β adrenergic receptor modulation of neurotransmission to cardiac vagal neurons in the nucleus ambiguus - Bateman, Ryan J. (2012)
β adrenergic receptors are a class of G protein-coupled receptors that have essential roles in regulating heart rate, blood pressure, and other cardiorespiratory functions. Although the role of β adrenergic receptors in the peripheral nervous system is well characterized, very little is known about their role in the central nervous system despite being localized in many brain regions involved in autonomic activity and regulation. Since parasympathetic activity to the heart is dominated by cardiac vagal neurons (CVNs) originating in the Nucleus Ambiguus (NA), β adrenergic receptors localized in the NA represent a potential target for modulating cardiac vagal activity and heart rate. This study tests the hypothesis that activation of β adrenergic receptors alters the membrane properties and synaptic neurotransmission to CVNs. CVNs were identified in brainstem slices and membrane properties and synaptic events were recorded using the whole-cell-voltage-clamp technique. The non-selective β agonist isoproterenol significantly decreased inhibitory GABAergic and glycinergic, as well as excitatory glutamatergic neurotransmission to cardiac vagal neurons. In addition, the β(1) selective receptor agonist dobutamine, but not β(2) or β(3) receptor agonists, significantly decreased inhibitory GABAergic and glycinergic and excitatory glutamatergic neurotransmission to CVNs. These decreases in neurotransmission to CVNs persisted in the presence of tetrodotoxin (TTX). These results provide a mechanism by which activation of adrenergic receptors in the brainstem can alter parasympathetic activity to the heart. Likely physiological roles for this adrenergic receptor activation are coordination of parasympathetic-sympathetic activity and β receptor mediated increases in heart rate upon arousal.